2-(4-{[4-Methyl-6-(1-methyl-1H-1,3-benzodiazol-2-yl)-2-propyl-1H-1,3-benzodiazol-1-yl] methyl} phenyl) benzoic acid as green corrosion inhibitor for mild steel in 1 M hydrochloric acid - Verma, Chandrabhan; Quraishi, M.A.; Gupta, Neeraj Kumar (Ain Shams University, 2016)
Present study describes the inhibition property of benzo 1,3-diazol 2-(4-{[4-Methyl-6-(1- methyl-1H-1,3-benzodiazol-2-yl)-2-propyl-1H-1,3-benzodiazol-1-yl] methyl} phenyl) benzoic acid (Telmisartan, Cresar-H) on mild steel corrosion in 1 M HCl using weight loss, electrochemical, and surface measurements. Results showed that the corrosion inhibition efficiency (g%) increases with increasing Telmisartan concentration and attained the maximum value of 97.39% at 125 mg L 1 concentration. Polarization studies revealed that Telmisartan acted as cathodic type inhibitor. Electrochemical impedance spectroscopy (EIS) studies suggested that the Telmisartan inhibits mild steel corrosion by becoming adsorbate at the metallic/electrolyte surfaces. Among the several tested isotherms, adsorption of the Telmisartan on mild steel surface obeyed the Temkin adsorption isotherm. The values of the apparent activation energy (Ea) suggested that Telmisartan inhibited metallic corrosion by creating energy barrier for corrosion process. The adsorption of corrosion inhibition was well supported by SEM/EDX and AFM studies.
Keywords: Acid corrosion; EIS/Bode/Tafel curves; Mild steel; SEM/EDX/AFM; Telmisartan